An Analysis of Ethno-Religious Conflict in Kaduna State - Adamu, Bala; Musa, Ibrahim (Kashere Journal of Politics and International Relations, 2025)
Ethno-religious conflict is one of the major security challenges that consumes lives and property of Kaduna People. The salient factor responsible for the conflict is linked with the densely populated society scrambling for scarce resource. Therefore, this paper has analyses ethno-religious conflict in Kaduna State of Nigeria. Data were obtained from the secondary source. The paper adopts social conflict theory at a guide for analysis. The findings indicate that economic hardship, ignorance, religious and intolerance among other are responsible for the conflict. The paper recommends for economic development, national dialogue and civic education.